2020
DOI: 10.1016/j.cgh.2020.06.058
|View full text |Cite
|
Sign up to set email alerts
|

Increased Internet Search Interest for GI Symptoms May Predict COVID-19 Cases in US Hotspots

Abstract: G oogle Trends is an online tool that allows measurement of search term popularity on Google, spatially and temporally. While not an epidemiological tool for determining incidence, it can estimate the popularity of a certain disease by search volume over time. 1,2 It has previously correlated well with infectious disease incidence and has demonstrated utility in disease forecasting, especially with influenza data. 3 We utilized Google Trends to investigate whether search interest in common gastrointestinal (GI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 5 publications
0
33
0
2
Order By: Relevance
“…Other authors [10], focusing on Google queries concerning loss of smell and taste in the US and Italy, draw opposite conclusions and suggest that Google Trends may not be reliably used to predict COVID-19 cases. Nevertheless [11] show that search interest in common gastrointestinal symptoms tend to correlate with coronavirus data recorded in the U.S. hotpots. Finally, a statistically significant correlation between Google search related to smell loss with COVID-19 cases and death has been proven for eight countries [12].…”
Section: Introductionmentioning
confidence: 81%
“…Other authors [10], focusing on Google queries concerning loss of smell and taste in the US and Italy, draw opposite conclusions and suggest that Google Trends may not be reliably used to predict COVID-19 cases. Nevertheless [11] show that search interest in common gastrointestinal symptoms tend to correlate with coronavirus data recorded in the U.S. hotpots. Finally, a statistically significant correlation between Google search related to smell loss with COVID-19 cases and death has been proven for eight countries [12].…”
Section: Introductionmentioning
confidence: 81%
“…Thus, we encourage caution regarding the interpretation of COVID-19 modeling experiments based on Google search engines. For example, Ahmad et al, 2020, found a correlation between gastrointestinal search terms obtained through GT and COVID-19 cases and suggested that Internet searches may be useful in predicting COVID-19 cases using a four-week lag in the U.S. This correlation might be an artifact since none of the gastrointestinal terms are specific to COVID-19, and the only COVID-19 specific term— ‘ageusia’—increased during the time that the pandemic was declared (i.e., 11 March) and decreased while cases started to increase (Figure 1 in Ahmad et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Brodeur et al, 2021, used GT to see how lockdowns affected well-being in the U.S. Once lockdowns were implemented, well-being likely decreased, as searches for certain terms such as ‘stress’, ‘suicide’, and ‘worry’ increased over the lockdown period. Ahmad et al, 2020 used gastrointestinal-related symptom search terms to determine whether GT could predict COVID-19 incidence, and found correlations between the search terms and increases of COVID-19 cases in multiple regions across the U.S. with a four-week lag.…”
Section: Introductionmentioning
confidence: 99%
“…Another group of studies did examine symptom-related search terms, including: “COVID pneumonia” and “COVID heart” in the US 36 ; “COVID” and “pneumonia” in China 37 ; “worry”, “hysteria” and other mental health symptoms in the US 38 ; “diarrhea”, “nausea”, “vomiting”, “abdominal pain”, “fever” and “cough” in the US 39 ; “can’t smell” “ear pain”, “sinus pain”, “voice pain”, “ears ringing”. Among other terms in the US 40 ; “ageusia”, “abdominal pain”, “loss of appetite”, “anorexia”, “diarrhea”, and “vomiting” in the US 41 ; “chest pain,” “myocardial infarction,” “cough,” and “fever” in four countries 42 ; “Loss of sense of smell”,”Sense of smell”, “Loss of sense of taste”, and “Sense of taste” across multiple regions in five countries 25 ; and “smell”, “loss of smell”, “anosmia”, “hyposmia”, “olfaction”, “taste”, “loss of taste”, and “dysgeusia” in eight countries 43 . While these studies investigated a range of important questions, including the effects of COVID-19 on mental health 38 , gastrointestinal health 39 , 41 , otolaryngological health 40 , and coronary-related conditions 42 , they did not study whether the temporal relationships between these search terms could be useful in understanding the clinical progression of the disease.…”
Section: Discussionmentioning
confidence: 99%